The Development of Teachers’ Knowledge of the Nature of Mathematical Modeling Scale - Reuben Asempapa (International Journal of Assessment Tools in Education)
This study addresses a gap in the literature on mathematical modeling education by developing the mathematical modeling knowledge scale (MMKS). The MMKS is a quantitative tool created to assess teachers’ knowledge of the nature of mathematical modeling. Quantitative instruments to measure modeling knowledge is scare in the literature partially due to the lack of appropriate instruments developed to assess such knowledge among teachers. The MMKS was developed and validated with a total sample of 364 K–12 teachers from several public-schools using three phases. Phase 1 addresses content validity of the scale using reviews from experts and interviews with knowledgable teachers. Initial psychometric properties and piloting results are presented in phase 2 of the study, and phase 3 reports on the findings during the field test, factor structure, and factor analyses. The results of the factor analyses and other psychometric measures supported a 12-item, one-factor scale for assessing teachers’ knowledge of the nature of mathematical modeling. The reliability of the MMKS was moderately high and acceptable (α = .84). The findings suggest the MMKS is a reliable, valid, and useful tool to measure teachers’ knowledge of the nature of mathematical modeling. Potential uses and applications of the MMKS by researchers and educators are discussed, and implications for further research are provided.